The relationship between emotional intelligence and leadership style among deans in UiTM / Mohd Kamal Muhsin Mohd Yunus - Mohd Yunus, Mohd Kamal Muhsin (2014)
The purpose of this study was to examine the level of emotional intelligence among deans in UiTM and also to identify the most preferred leadership style by deans in UiTM and lastly to investigate the relationship between emotional intelligence and leadership style among deans in UiTM. Six faculties were selected from applied science and social science disciplines. Data were collected using questionnaire techniques. The questionnaire was distributed to a total of 300 randomly selected lecturers' respondents and 252 questionnaires were returned. Data were analyzed using descriptive and inferential statistics. The findings revealed that the level of emotional intelligence was at high level among deans of six selected faculties. In addition, findings indicated that most preferred leadership style by deans in UiTM was transformational leadership style perceived by lecturers as respondents. Lastly, findings indicated transformational leadership style was scored (r=0.34) slightly higher compared to transactional leadership style (r=0.22) and both dimensions were having significant relationship between emotional intelligence among deans in UiTM. Overall, the findings of this study have implications to the role of deans, lecturers and administrators in the way to enhance positive climate. Based on the findings, this study also provides recommendations for improvement of practices and future research.